Containing the Jeremiad: Understanding Paradigms of Anxiety in Global Climate Change Experience - Brian Glaser (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
This essay uses Bion’s concept of “containing” to read the psychological dynamics of jeremiads about global climate change, arguing that their structure reveals a strategy of communication that may be useful for more broadly raising awareness about this challenging state of the planet. More specifically, I argue that contemporary global climate change jeremiads have a structure that first elicits alarm and then moves to discuss solutions, and that this structure may be beneficial to those who are awakening to the reality of global climate change by rendering anxiety bearable and therefore open to purposive and creative response.